A Review of Green Technologies for Cellulose Extraction from Lignocellulosic Biomass: Pretreatment Methods and Applications (Global Journal of Sciences, 2026)
The majority of the material called lignocellulose biomass (LCB), a type of plant  biomass, is made up of these three compounds. The most common polymer to break  down on Earth is cellulose, which is very useful and has many uses. Because cellulose  is securely linked to the compound’s hemicellulose and lignin in lignocellulosic  materials, it is highly challenging to separate the material from LCB components;  therefore, effective pretreatment techniques are required to make the material  separation easier. Green pretreatment approaches have been proposed as a gentler and  more environmentally responsible way to address these problems. When assessing  these green processes, a variety of factors are taken into account, such as the  effectiveness of delignification with a lower solvent demand, the impact on the  environment, the economic feasibility, and the suitability for new sustainable  processing solutions. We also assessed how using biomass affected land use,  production of greenhouse gases, and group effects, among other socioeconomic and  environmental factors. This paper examines the challenges, ongoing research, and  recent developments in effective biomass-based energy systems to increase energy  output while lowering environmental concerns. Additionally, it provides a summary of  how cellulose is separated from various lignocellulosic biomass using sustainable and  green methods.
Keywords: Green energy; Energy crises; Biomass sources; Biomass